Analisis peningkatan aktivitas siswa kelas IX dalam menulis teks cerita inspiratif melalui media audiovisual - Gusnimar, Gusnimar (Universitas Negeri Padang, 2021)
This study aimed to determine the increase in student activity in writing inspirational story texts through audiovisual media in class IX.3 in the 2nd Semester of the 2020/2021 Academic Year at SMPN 1 Kec. Situjuah Limo Nagari. The research method used in this research is Classroom Action Research (CAR), with four activities: planning, action, observation, and reflection. The research subjects were 30 students of class IX.3 consisting of 10 boys and 20 girls. Based on the findings during the study, it can be concluded that students' activity in writing inspirational story texts can be increased through audiovisual media.